Post operative complications associated with non- surgical tooth extraction (Mustansiria Dental Journal, 2018)
Aim: The purpose of this study was to evaluate the clinical pattern of post-extraction wound healing and determination the types, incidence, and pattern of healing complications following non-surgical tooth extraction.Materials and Methods: this study includes 156 patients, who were come for extractions of teeth. This study was carried out at specialized dental centre of AL-Thawra during the period from the beginning of May to the end of September 2007). For each patient collected information pre-operatively included age and gender of the patient, indications of extraction, and tooth/teeth removed. Extractions were performed under local anesthesia with dental forceps, elevators, or both. Patients were evaluated on the third and seventh postoperative days for alveolus healing assessmentResults: one hundred forty-one patients (141) with 159 extraction teeth were evaluated for alveolus healing. Uncomplicated healing was in 142 (89.3 %), while 17 alveoli (10.7 %) developed healing complications. These complications were: localized osteitis 13 (8.2 %); acutely infected alveolus 3 (1.9 %); and an acutely inflamed alveolus1 (0.6%). Females developed more complications than males (p=0.003). Most complications were found in molars (82.5 %) and premolars (17.5 %). Localized osteitis caused severe pain in all cases, while infected and inflamed alveolus caused mild or no pain.Conclusions: Most of the post-extraction alveoli healed uneventfully. Apart from alveolar osteitis (AO), post-extraction alveolus healing was also complicated by acutely infected alveoli and acutely inflamed alveoli. This study also demonstrated a painful alveolus is not necessarily a disturbance of post-extraction site wound healing; a thorough clinical examination must, therefore, be made to exclude any of the complications.